Circulating microRNAs in Early Breast Cancer Patients and Its Association With Lymph Node Metastases - Escuin, Daniel; López-Vilaró, Laura; Mora, Josefina; Bell, Olga; Moral, Antonio; Pérez, Ignacio; Arqueros, Cristina; García-Valdecasas, Bárbara; Ramón y Cajal, Teresa; Lerma, Enrique; Barnadas, Agustí (Frontiers in Oncology, 2021)
MicroRNAs have emerged as important regulators of the metastatic process. In addition, circulating miRNAs appear to be surprisingly stable in peripheral blood making them ideal noninvasive biomarkers for disease diagnosis. Here, we investigated the expression profile of circulating miRNAs and their association with the metastatic lymph node status in early breast cancer patients. Sentinel lymph node status was detected by one-step nucleic acid (OSNA) analysis. We performed RNA-sequencing in 16 plasma samples and validated the results by qPCR. Gene Ontology term enrichment and KEGG pathway analyses were carried out using DAVID tools. We found16 differentially expressed miRNAs (q < 0.01) in patients with positive samples. Thirteen miRNAs were down-regulated (miR-339-5p, miR-133a-3p, miR-326, miR-331-3p, miR-369-3p, miR-328-3p, miR-26a-3p, miR-139-3p, miR-493-3p, miR-664a-5p, miR-323b-3pmiR-1307-3p and miR-423-3p) and 3 were up-regulated (miR-101-3p, miR-146a-5p and miR-144-3p). Hierarchical clustering using differentially expressed miRNAs clearly distinguished patients according to their lymph node status. Gene ontology analysis showed a significant enrichment of biological processes associated with the regulation of the epithelial mesenchymal transition, cell proliferation and transcriptional regulation. Our results indicated the potential role of several circulating miRNAs as surrogate markers of lymph node metastases in early breast cancer patients. Further validation in a larger cohort of patients will be necessary to confirm our results.